Respostas da frequência cardíaca durante o exercício isométrico de pacientes submetidos à reabilitação cardíaca fase III - Leite, Poliana Hernandes (Universidade Federal de São Carlos, 2009)
Cardiovascular responses to different isometric contractions were evaluated in 12 patients (63 ± 11,6 years, mean ± dp) with coronary artery disease and/or risk factors, participants in the cardiac rehabilitation phase III. Heart rate variation (ΔHR) was evaluated during maximum (CVM, five and ten seconds in duration) and submaximal (CVSM, 30 and 60% of CVM-5, until muscle exhaustion) voluntary contraction, using a handgrip dynamometer. Additionally, the RMSSD (representative index of vagal modulation) was calculated at rest (precontraction), at the last 30 seconds of CVSM and recovery (post-contraction). ΔHR showed higher values in CVM CVM-10 vs-5 (17 ± 5,5 vs 12 ± 4,2 bpm, p <0.05) and the CVSM-60 vs CVSM -30 (19 ± 5,8 vs 15 ± 5,1 bpm, p <0.05). However, results for CVM-10 showed similar ΔHR compared to results for CVSM (p> 0.05). RMSSD at rest decreased (p <0.05) during CVSM-30 (30% = 28 ± 17 vs 13 ± 8 ms) and CVSM-60 (60% = 26 ± 18 vs 10 ± 4 ms), but returned to baseline values as the contraction was interrupted. In in patients with coronary artery disease and/or risk factors, low intensity isometric contraction, maintained over long periods of time, presents the same effect on the responses of HR, compared to a briefly high intensity or maximal isometric effort.
Keywords: Fisioterapia; Contração isométrica; Frequência cardíaca; Sistema cardiovascular - Doenças - Pacientes -Reabilitação; Controle autonômico; Isometric contraction; Heart rate; Cardiac rehabilitation; Autonomic control; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL